Korelasi antara Berat Badan, Tinggi Badan, Indeks Massa Tubuh dan Rasio Lingkar Pinggang-Panggul dengan Hiperkifosis Torakal dan Hiperlordosis Lumbar pada Pelajar Sekolah Menengah Atas - Tena Djuartina; Andrew Wijaya; Nawanto Agung Prastowo; Sylvia Wijaya (Majalah Kedokteran Indonesia, 2020)
Background: Adolescents’ lifestyle has been changing overtime, impacting their body weight, height, body mass index, and waist hip ratio. This changes also outgrow with the changes of sagittal curvature of thoracic kyphosis and lumbar lordosis. Thoracic hyperkyphosis and lumbar hyperlordosis is a disease not only affecting convenience, but also psychologically impacted (body image disorder). The only way to stop this is by aiming for preventive measure, by knowing the correlation between these variables to thoracic hyperkyphosis and lumbar hyperlordosis.Method: A cross sectional study was conducted in two schools, SMAN 2 Jakarta and SMA Katolik Diakonia. This study used weight scales to measure body weight and scaled-tape to measure body height. The sagittal curvature was measured by flexicurve.Result: Out of 154 respondents, 49.35 % were male students and the rest 50.65% were female students. Hyperkyphotic students were found 24.68%, and hyperlordotic students were found 24.02%. No correlation was found between variables but IMT to lumbar hyperlordosis. Weak correlation also found between waist and hip circumference and lumbar hyperlordosis.Conclusion: Weak correlation was found between Body Mass Index (BMI) and lumbar hyperlordosis in high school students. No correlation found between waist-hip ratio and lumbar hyperlordosis, but weak correlation was found between waist and hip circumference and lumbar hyperlordosis. No correlation was found between variables and thoracic hyperkyphosis.